Climate change impacts, adaptation, and mitigation in global agriculture - Martínez, Luis Carlos; Plata-Rueda, Angelica (Revista de Ciencias Agrícolas, 2026)
Climate change has become an immediate and systemic stressor on global agrifood systems, with agriculture being both highly vulnerable to climate impacts and a major source of greenhouse gas emissions. Rising temperatures, water instability, soil degradation, and shifting pest and disease pressures are already reducing crop and livestock productivity, especially for smallholder farmers in Latin America, Sub-Saharan Africa, and South Asia. Using the Climate-Smart Agriculture framework, this editorial note highlights integrated responses that combine digital agriculture, agroecology, advanced breeding, and modeling for adaptation and mitigation. It emphasizes that technology alone is inadequate without strong institutions, inclusive knowledge systems, coherent policies, and green economy investments. Addressing persistent research gaps and moving beyond incremental change toward transformative and equitable transitions is essential to safeguard food security, livelihoods, and ecosystems while meeting climate goals.